The Relationship Between Parenting Styles with Career Decision Making Difficulties in Class XII Students at The Laboratory Development High School of Padang State University - Dwi Aryani, Ervina; Rinaldi (Causalita, 2024)
This study aims to determine the relationship between Parenting Styles and Career Decision-Making Difficulties in Class XII Students at UNP Laboratory Development High School. Parenting Styles are ways of parenting used in raising a child that are likely to have an impact on the child's future success in romantic relationships, peers, and parenting. Career Decision-Making Difficulties are a condition that inhibits individuals from making decisions about future careers, not being able to determine careers, and not being able to determine career decisions that are suitable for themselves. This study uses quantitative methods with a research design using quantitative correlation. The population in this study were XII grade students at UNP Laboratory Development High School with a total subject of 142 students. The sampling technique used was purposive sampling. Data collection tools use Parenting Styles and Career Decision-Making Difficulties scales. Data analysis using product moment correlation coefficient. The results showed that there was a significant positive relationship between Parenting Styles and Career Decision-Making Difficulties in Class XII Students at UNP Laboratory Development High School (r = 0.060; p = 0.0482).